Solve for y -2/7y=1/2

-27y=12
Multiply both sides of the equation by -72.
-72⋅(-27)⋅y=-72⋅12
Simplify both sides of the equation.
Simplify -72⋅(-27)⋅y.
Cancel the common factor of 7.
Move the leading negative in -72 into the numerator.
-72⋅(-27)⋅y=-72⋅12
Move the leading negative in -27 into the numerator.
-72⋅-27⋅y=-72⋅12
Factor 7 out of -7.
7(-1)2⋅-27⋅y=-72⋅12
Cancel the common factor.
7⋅-12⋅-27⋅y=-72⋅12
Rewrite the expression.
-12⋅-2⋅y=-72⋅12
-12⋅-2⋅y=-72⋅12
Cancel the common factor of 2.
Factor 2 out of -2.
-12⋅(2(-1))⋅y=-72⋅12
Cancel the common factor.
-12⋅(2⋅-1)⋅y=-72⋅12
Rewrite the expression.
-1⋅-1⋅y=-72⋅12
-1⋅-1⋅y=-72⋅12
Multiply.
Multiply -1 by -1.
1⋅y=-72⋅12
Multiply y by 1.
y=-72⋅12
y=-72⋅12
y=-72⋅12
Multiply -72⋅12.
Multiply 12 and 72.
y=-72⋅2
Multiply 2 by 2.
y=-74
y=-74
y=-74
The result can be shown in multiple forms.
Exact Form:
y=-74
Decimal Form:
y=-1.75
Mixed Number Form:
y=-134
Solve for y -2/7y=1/2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top